Non-communicable diseases prevention in remote areas of Vietnam: Limited roles of health education and community workers. - Hang Thi Le; Tuan Anh Le; Tuan Dang Mac; Dua Nhu Nguyen; Ha Ngoc Vu; Anh Thi Mai Truong; Anh Tran Quang Do; Hoai Thi Thu Bui; Huong Thi Thu Do; Anh Thi Hoang Nguyen; Trung Thanh Nguyen; Ngoc The Ngo; et al. (PLoS ONE, 2022)
Objective This study aimed to measure the exposure of residents to health education messages about non-communicable diseases (NCD)-related risk factors, and activities of village health workers (VHWs) in NCDs prevention and control in the mountainous setting of Vietnam. Method A cross-sectional study was performed in Dap Thanh commune (Ba Che, Quang Ninh province, Vietnam), a mountainous area. There were 151 residents aged 18 years or above recruited for this study. Information regarding exposure to messages about risk factors of NCDs, and activities of VHWs was collected via face-to-face interviews using a structured questionnaire. Multivariate logistic regression was employed to identify associated factors with exposing messages about NCD-related risk factors. Results The majority of participants heard about messages related to risk factors of NCDs in the last 30 days, from 56.3% (physical inactivity message), 59.6% (diet message), 75.5% (alcohol use message) to 79.5% (smoking message). Radio/television was the most common source of the messages (from 91.8% to 95.8%) and the majority of participants heard these messages from one source (from 77.1% to 80.9%). Most of sample reported the unavailability of VHWs in their locals (53.6%). Among locals having VHWs, health communication and education was the most common service provided (54.3%); however, only 30% received NCD management services. Participants who had other jobs were less likely to hear about diet-related messages (OR = 0.32; 95%CI = 0.11-0.92), and those ever smoking were more likely to hear these messages in the last 30 days (OR = 6.86; 95%CI = 1.06-44.51). People who had diabetes mellitus were more likely to hear physical activity-related messages in the last 30 days (OR = 2.55; 95%CI = 1.20-5.41). Conclusion Our findings indicated that health communication regarding risk factors of NCDs in mountainous areas in Vietnam was insufficient, and the role of health workers as formal information source was not recognized. Efforts should be made to increase the capacity and involvement of VHWs in health education and NCD prevention in mountainous regions.